Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jccs.202000382
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photovoltaic performance of dye‐sensitized solar cell based on ZnO nanoparticles and ZnO/graphene nanocomposites

Abstract: For clean, inexpensive, and renewable power source, dye‐sensitized solar cell (DSSC) has attracted more attention in recent decades. DSSC faces various challenges that lead scientists to further research. In this study, the efficiency of DSSC was improved through the development of a new ZnO nanoparticles and ZnO/graphene nanocomposite as a photoanode electrode and poly(3,4‐ethylenedioxythiophene) (PEDOT), PEDOT/multi wall carbon nanotube (MWCNT), and Pt as a counter electrode. Synthesized samples were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that incorporating carbon-based nanomaterials can enhance the field-effect mobility. Nanocomposites based on nanoparticles indicated an improved performance in solar cells, LEDs, thermoelectric devices, and thin-film transistors (TFTs) [10][11][12]. Polymer composites are created by synthesizing polymers with nanoparticles, which helps to enhance their electronic and optical properties.…”
Section: Eejp 1 (2024)mentioning
confidence: 99%
“…Previous studies have shown that incorporating carbon-based nanomaterials can enhance the field-effect mobility. Nanocomposites based on nanoparticles indicated an improved performance in solar cells, LEDs, thermoelectric devices, and thin-film transistors (TFTs) [10][11][12]. Polymer composites are created by synthesizing polymers with nanoparticles, which helps to enhance their electronic and optical properties.…”
Section: Eejp 1 (2024)mentioning
confidence: 99%
“…The introduction of graphene in the ZnO nanoparticles has decreased the semiconductor's bandgap and, therefore, increased the DSSC's efficiency with the Pt counter electrode. 59 The EIS is widely used to investigate the interfacial electrical properties and determine the kinetics of charge transfer in DSSCs. Commonly, the equivalent circuit model configuration for DSSCs was split into three main branches: shunt resistance, R s , sub-branch of counter electrode capacitor with a resistor, followed by resistivity capacitor with resistor.…”
Section: Interaction Between Dye and Zno/ Graphene Derivativesmentioning
confidence: 99%
“…A recent finding by Yousif et al achieved the highest PCE of 11.53% for the ZnO/graphene nanocomposite. The introduction of graphene in the ZnO nanoparticles has decreased the semiconductor's bandgap and, therefore, increased the DSSC's efficiency with the Pt counter electrode 59 …”
Section: Introductionmentioning
confidence: 99%
“…As a known semiconductor, TiO₂ is one of the most common and suitable material for environmental issues because of its high photocatalytic performance, low cost, easy availability, and non-toxicity. [1][2][3][4] TiO₂ based photocatalysts have wide bandgap energy of 3.7 eV, and high recombination rate, limiting their application to be used as photocatalyst for organic dye degradation. Hence, many researchers tried to enhance the photocatalytic performance using different approaches such as elemental doping, immobilization of other semiconductor, and use of some metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%